INFLUENCE OF NACL MEDIATED SALINITY STRESS ON LIPID PEROXIDATION IN GERMINATING SEEDS OF SOYBEAN - PATIL DHAIRYASHEEL B.; BHAMBURDEKAR SHARAD B (International Journal of Pharma and Bio Sciences, 2015)
Salinity is one of the major abiotic stress that affects the growth and development of many important legume plants. Soybean is a most important oilseed legume cash crop of the world. It is also considered as an important source of high quality cheap protein and oil. In the present investigation, the effect of different concentrations of NaCl (50 mM, 100 mM, 150 mM and 200 mM) on lipid peroxidation during germination of soybean seeds was studied. The lipid peroxidase activity remarkably increases as concentration of salinity increases. The result revealed that, the activity of lipid peroxidation significantly increases up to 72 hrs in all treatments except 50 mM NaCl treatment.